Frontiers of Complex Disease Mechanisms: Membrane Surface Tension May Link Genotype to Phenotype in Glaucoma - Petty, Howard R. (Frontiers in Cell and Developmental Biology, 2018)
Although many monogenic diseases are understood based upon structural changes of gene products, less progress has been made concerning polygenic disease mechanisms. The purpose of this Specialty Grand Challenge article is to present a new interdisciplinary approach to understand complex diseases, especially their genetic polymorphisms correlating with disease. I focus upon primary open angle glaucoma (POAG). Although elevated intraocular pressure (IOP) and oxidative stress are glaucoma hallmarks, the linkages between these factors and cell death are obscure. Lipid peroxidation creates oxidatively truncated phosphoglycerides, free fatty acids, lysophosphoglycerides, oxysterols, and other chemical species that decrease membrane surface tension. Several POAG-linked gene polymorphisms identify proteins that manage damaged lipids and/or influence membrane surface tension. POAG-related genes expected to participate in these processes include: ELOVL5, ABCA1, APOE4, GST, CYP46A1, MYOC, and CAV. I propose that heightened IOP overcomes retinal ganglion cell membrane tensile strength, weakened by damaged lipid accumulation, to form pores. The ensuing structural failure promotes apoptosis and blindness. The linkage between glaucoma genotype and phenotype is mediated by physical events. Force balancing between the IOP and surface tension regulates pore nucleation; force balancing between pore line tension and membrane surface tension regulates pore growth. Similar events may contribute to traumatic brain injury, Alzheimer’s disease, and macular degeneration.